1979
DOI: 10.1099/00221287-114-1-117
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucosyl- and Fructosyltransferase Synthesis by Continuous Cultures of Streptococcus mutans

Abstract: 117Streptococcus mutans strain Ingbritt, and its derivative B7 which had been passaged through monkeys, have been used to investigate how the synthesis of extracellular glucosyl-and fructosyltransferases is regulated. The most active enzyme from carbon-limited continuous cultures was a fructosyltransferase ; enzymes catalysing the formation of water-insoluble glucans from sucrose were relatively inactive. Dextransucrase (EC 2.4.1 .5), which catalyses soluble glucan synthesis, was most active in the supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 9 publications
(9 reference statements)
2
30
0
Order By: Relevance
“…This proposal is mainly based on the striking similarity in the Nterminal amino acid sequences of E. amylovora, Z. mobilis, and P. syringae pv. phaseolicola, in contrast to the nearly completely missing similarity to those of the gram-positive bacteria B. subtilis, B. amyloliquefaciens, and S. mutans, which are very similar to each other in activity and sequence (3,43,45,49,51). A comparison of the Z. mobilis and E. amylovora enzymes shows a high similarity in the first 75 amino acids: 55% are identical.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This proposal is mainly based on the striking similarity in the Nterminal amino acid sequences of E. amylovora, Z. mobilis, and P. syringae pv. phaseolicola, in contrast to the nearly completely missing similarity to those of the gram-positive bacteria B. subtilis, B. amyloliquefaciens, and S. mutans, which are very similar to each other in activity and sequence (3,43,45,49,51). A comparison of the Z. mobilis and E. amylovora enzymes shows a high similarity in the first 75 amino acids: 55% are identical.…”
Section: Discussionmentioning
confidence: 97%
“…phaseolicola are of nearly the same molecular weight, about 47,000. Also, all of them are secreted constitutively, in contrast to the mostly substrate-dependent expression of levansucrases in gram-positive bacteria (38,43,51).…”
Section: Discussionmentioning
confidence: 99%
“…1 l), which partially degrades glucan ; and fructanase (p-D-fructan fructohydrolase; EC 3.2.1.80), which releases free fructose by hydrolysing fructan polymers. Since these enzymes are produced in the absence of substrate, they have been assumed to be constitutive in oral streptococci (Janda & Kuramitsu, 1978;Wenham et al, 1979). Although there have been suggestions in the literature that this might not be the case (Keevil et al, 1983;Walker et al, 1983;Walker & Jacques, 1987), it has been difficult to show conclusively that these enzymes are under any kind of regulatory control.…”
Section: Introductionmentioning
confidence: 94%
“…Growth of S. mutans Ingbritt in continuous culture indicated that the enzyme is constitutively expressed (27). In contrast, another enzyme catalyzing the synthesis of fructan from sucrose, levansucrase from Bacillus subtilis, was shown to be inducible by sucrose (12).…”
mentioning
confidence: 99%